N-WAVE AND OTHER SOLUTIONS TO THE B-TYPE KADOMTSEV-PETVIASHVILI EQUATION - İnç, Mustafa; Hosseini, Kamyar; Samavat, Majid; Mirzazadeh, Mohammad; Eslami, Mostafa; Moradi, Mojtaba; Baleanu, Dumitru (Vinca Inst Nuclear Sci, 2019)
The present article studies a B-type Kadomtsev-Petviashvili equation with certain applications in the fluids. Stating with the Hirota's bilinear form and adopting reliable methodologies, a group of exact solutions such as the N-wave and other solutions to the B-type Kadomtsev-Petviashvili equation is formally derived. Some figures in two and three dimensions are given to illustrate the characteristics of the obtained solutions. The results of the current work actually help to complete the previous studies about the B-type Kadomtsev-Petviashvili equation.
Keywords: B-type Kadomtsev-Petviashvili equation; Hirota's bilinear form; reliable methodologies; N-wave and other solutions